Effect of Non-Rubber Constituents on Guayule and Hevea Rubber Intrinsic Properties - M.A. Monadjemi, Shirin; M. McMahan, Colleen; Cornish, Katrina (Journal of Research Updates in Polymer Science, 2016)
To meet the increasing demand for natural rubber (NR), currently sourced from the tropical rubber tree Hevea brasiliensis, and address price volatility and steadily increasing labor costs, alternate rubber-producing species are in commercial development. One of these, guayule (Parthenium argentatum), has emerged on the market as a commercial source of high quality rubber. Non-rubber constituents play an important role in the physical properties of NR products. The intrinsic composition of the two NR materials differs and these differences may be a principal cause of the performance differences between them. We have compared the effect of non-rubber constituents, such as protein, lipids, resin and rubber particle membranes. Firstly, a film casting method was developed to obtain rubber films with a uniform thickness. Secondly, the glass transition temperature of different rubbers was determined by dynamic mechanical analysis, and tensile properties were tested for uncompounded materials. Guayule natural rubber (GNR), from which most of the membranes were removed while in latex form (MRGNR) was found to have higher intrinsic strength than GNR or gel-free NR (FNR). An acetone extraction was performed to quantify the resin and free lipids in the rubber samples.